An improved method for active phased-array antennas calibration - Usina, Anna; Markov, Vasyl; Usin, Vladimir (Видавництво Львівської політехніки, 2012)
Some problems of phased array antennas and its T/R modules calibration are considered. The main attention is paid to the problems and procedures of diagnostics and measurements of amplitude and phase distribution on aperture, to alignment and calibrations of phased array antennas, which take into account the peculiarities connected with its hardware implementation and service conditions.
Keywords: Calibration; active phased-array antenna; antenna measurements; alignment; calibration; fault diagnostics; performance monitoring; weighting functions; signal isolation; module failure; transfer matrix.